The consequences of the misuse of social media as a medium for news and information / Siti Kharteeny Mohd Shuraddin and Zulkifli Abd Latiff - Mohd Shuraddin, Siti Kharteeny; Abd Latiff, Zulkifli (Universiti Teknologi MARA, 2022)
The emergence of the internet has allowed the existence of social media such as Facebook, Instagram, Twitter and many more. Modern society is able to connect and exchange knowledge and this has made life easier and better as we can use social media to connect with people across the globe, do business, make new friends or even as one of the sources of news. However, regardless of the advantages of social media, there are still people out there that took it for granted especially the misuse of these social platforms. Hence, this study aims to identify the factor that contributes to the use of social media as one of the sources of news and to measure the extent of the misuse of social media platforms as a medium for news and information. Qualitative research methodology has been applied in this study and the researcher conducted in-depth interviews in order to gain desired data. Findings of this study shows that social media has been one of the sources of news for the people due to the ability of this platform to rapidly disseminate news and information to the audiences. People are also aware of the social media misuse such as disseminating fake news and presence of parody accounts.